Interference of chemical defence and sexual communication can shape the evolution of chemical signals - Pfeiffer, Lisa; Ruther, Joachim; Hofferberth, John; Stökl, Johannes; Justus Liebig University Giessen (My University, 2018)
According to current evolutionary theory, insect pheromones can originate from extant precursor compounds being selected for information transfer. This is exemplified by females of the parasitoid wasp Leptopilina heterotoma whose defensive secretion consisting mainly of (-)-iridomyrmecin has evolved secondary functions as cue to avoid other females during host search and as female sex pheromone. To promote our understanding of pheromone evolutionÂ from defensive secretions we studied the chemical ecology of Leptopilina clavipes. We show here that L. clavipes also produces a defensive secretion that contains (-)-iridomyrmecin as major component and that females use it to detect and avoid host patches occupied by other females. However, the female sex pheromone of L. clavipes consists solely of cuticular hydrocarbons (CHCs) and males did not respond to female CHCs if presented in combination with the defensive secretion containing (-)-iridomyrmecin. This is in contrast to other species of Leptopilina, in which the iridoid compounds have no inhibiting effect or even function as sex pheromone triggering courtship behaviour. This indicates that Leptopilina species differ in the cost-benefit ratio for males searching for females, which might explain the strong divergence in the composition of the sex pheromone in the genus.
Keywords: ddc:590